Method for evaluating delayed fracture characteristics of metal material, method for selecting metal material, method for manufacturing member, metal material, and member for automobile

CN122910404APending Publication Date: 2026-10-13JFE STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480089457.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-21
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

[0026]根据本发明,能够提供金属材料的延迟断裂特性的评价方法,其能够针对例如在汽车行驶的大气腐蚀环境下使用的金属材料精度良好地评价由伴随氯化物成为腐蚀的支配因子的大气腐蚀而侵入金属材料的内部的氢引起的延迟断裂特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122910404A_ABST
    Figure CN122910404A_ABST
Patent Text Reader

Abstract

Provided is a method for evaluating delayed fracture properties of a metal material caused by hydrogen that has intruded into the interior of the metal material due to atmospheric corrosion in which chloride is a dominant factor of corrosion, with good precision. A method for evaluating delayed fracture properties of a metal material, wherein a process having a chloride-attachment process (A) and a corrosion process (B) is performed one or more times, in the chloride-attachment process (A), droplets of an aqueous solution containing chloride are attached to an evaluation surface of a metal material in such a manner as to achieve a prescribed chloride-attachment amount, and in the corrosion process (B), a cycle having a prescribed drying process (b1), a wetting process (b2), a transition process (b3), and a transition process (b4) is performed one or more times, and the distribution of the droplets on the evaluation surface of the metal material in the initial chloride-attachment process (A) is such that the average contact area of the droplets is 0.1 mm 2 or less, the area ratio of the total contact area of the droplets to the area of the evaluation surface is 40% or more and 80% or less, and the standard deviation of the contact area of the droplets is 3.0 mm 2 or less. 2 ​
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for evaluating the delayed fracture characteristics of metallic materials. More particularly, this invention relates to a method for evaluating the delayed fracture (presence and extent of delayed fracture, etc.) of metallic materials used in the atmospheric corrosive environment of automobile driving, caused by hydrogen penetrating into the interior of the metallic material along with corrosion. Background Technology

[0002] In recent years, efforts have been made to reduce the thickness of steel plates by increasing their strength, based on the goal of lightweighting automotive structural components. With this increase in steel strength, concerns about delayed fracture, which was not previously a problem in automotive parts, have resurfaced.

[0003] Delayed fracture refers to the phenomenon where high-strength steel components, under static stress, suddenly fracture with almost no plastic deformation after a certain period of time. In a broader sense, it also includes liquid metal contact cracks and stress corrosion cracks (Non-Patent Literature 1). In automotive components, a problem arises from hydrogen embrittlement-type delayed fracture caused by hydrogen intrusion into the steel along with corrosion. The known factors causing delayed fracture are material (strength), processing (strain / stress), and hydrogen. Here, the causes of hydrogen intrusion into metallic materials can be considered as intrusion from solutions / solvents in contact with the metal, and intrusion of hydrogen generated during corrosion of the metal in the operating environment.

[0004] Previously, research on delayed fracture has been extensively conducted in the field of thick plates such as pipeline steel with high hydrogen content from solution / solvent intrusion, and in high-strength steel bolts with tensile strengths exceeding 1200 MPa (Non-Patent Document 2). Furthermore, methods for evaluating delayed fracture characteristics have been standardized in these fields.

[0005] On the other hand, automotive components are used in atmospheric environments. Therefore, in order to properly evaluate the delayed fracture characteristics of automotive components, it is important to establish a method for evaluating the hydrogen embrittlement-type delayed fracture characteristics caused by hydrogen intruding into automotive components along with atmospheric corrosion. Therefore, an evaluation method for delayed fracture characteristics simulating atmospheric corrosion environments is proposed.

[0006] For example, Patent Document 1 discloses a method for evaluating the delayed fracture characteristics of a metallic material, wherein a process consisting of the following steps is performed at least once: a step of attaching a chloride-based component to the metallic material; and a step of performing a drying step of drying the surface of the metallic material by changing the relative humidity of the metallic material and a wetting step of wetting the surface of the metallic material as a cycle and performing the cycle at least once.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-180658

[0010] Non-patent literature

[0011] Non-patent literature 1: Matsuyama Shinsaku, Delayed fracture, Nikkan Kogyo Shimbun, 1989

[0012] Non-patent literature 2: Ōmura et al., Corrosion Prevention and Control Symposium Materials, vol. 170, pp. 47-54, 2010 Summary of the Invention

[0013] The problem that the invention aims to solve

[0014] In the corrosive atmospheric environment of automobile operation, corrosion is accelerated by the adhesion of salts such as de-icing salt and inhaled salt. It is believed that hydrogen generated from chloride-induced corrosion (atmospheric corrosion where chloride is the dominant corrosion factor) penetrates metallic materials, leading to delayed fracture. Therefore, for automotive components, evaluating the delayed fracture characteristics of areas with high chloride adhesion levels within a hypothetical chloride adhesion range becomes important. However, the results of evaluating the delayed fracture characteristics of high-strength steel sheets using the evaluation method described in Patent Document 1 show that, depending on the type of high-strength steel sheet, it is sometimes impossible to accurately determine the quality of the delayed fracture characteristics.

[0015] The present invention was made in view of the above circumstances, and its object is to provide a method for evaluating the delayed fracture characteristics of metallic materials, which can accurately evaluate the delayed fracture characteristics caused by hydrogen penetrating into the interior of metallic materials by atmospheric corrosion, which is dominated by chlorides, for example, in the atmospheric corrosion environment of automobile driving.

[0016] Methods for solving problems

[0017] Through in-depth research, the inventors discovered that the above-mentioned objectives can be achieved by adopting the following configuration, thus completing the present invention.

[0018] [1] An evaluation method for delayed fracture characteristics of metallic materials, wherein, Perform a process that involves at least one chloride deposition step (A) and an etching step (B). In the chloride adhesion process (A), the amount of chloride adhered is made to reach 1000-20000 mg / m³. 2 This method allows droplets of an aqueous solution containing chloride to adhere to the evaluation surface of the metallic material. In the corrosion process (B), in an atmosphere with a temperature Tb1 below 60°C and within a certain range, a cycle consisting of the following drying process (b1), wetting process (b2), transformation process (b3), and transformation process (b4) is considered as one cycle, and this cycle is performed at least once. Drying process (b1): A process of drying metal materials by maintaining them in an atmosphere with a relative humidity of less than 45% (Hb1) for more than 1.0 hour and less than 5.0 hours. Wetting process (b2): A process of wetting metal materials by maintaining an atmosphere with a relative humidity of 80% or higher (Hb2) for 1.0 hour to 5.0 hours. Transition process (b3): ​​A process of changing the atmosphere from relative humidity Hb1 to relative humidity Hb2 at a relative humidity change rate of less than 30% / hour. Transition process (b4): A process of changing the atmosphere from relative humidity Hb2 to relative humidity Hb1 at a relative humidity change rate of less than 30% / hour. At least in the initial chloride adhesion process (A), the distribution of droplets containing the chloride-containing aqueous solution on the evaluation surface of the metal material is such that the average contact area of ​​the droplets on the evaluation surface of the metal material is 0.1 mm. 2 Above and below 3.0mm 2 The total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is 40% to 80% of the total contact area, and the standard deviation of the contact area of ​​the droplets on the evaluation surface of the metal material is 3.0 mm. 2 the following.

[0019] [2] According to the evaluation method for delayed fracture characteristics of metal materials described in [1], in the chloride adhesion step (A), the aqueous solution containing chloride is sprayed with a spray nozzle. At this time, a shielding member with an opening is disposed between the metal material and the spray nozzle, so that droplets of the aqueous solution containing chloride sprayed from the spray nozzle pass through the opening of the shielding member and adhere to the evaluation surface of the metal material.

[0020] [3] The method for evaluating the delayed fracture characteristics of metallic materials according to [1] or [2], wherein the chloride adhesion process (A) is carried out in an atmosphere with a relative humidity of more than 30% Ha1 and a temperature of less than 50°C Ta1.

[0021] [4] A method for selecting a metallic material, comprising: an evaluation step of evaluating the delayed fracture characteristics of a metallic material using the evaluation method for the delayed fracture characteristics of metallic materials described in any one of [1] to [3] above; and a selection step of selecting a metallic material based on the evaluation result obtained in the evaluation step.

[0022] [5] A method for manufacturing a component, wherein the component is manufactured by processing a metal material selected by the metal material selection method described above [4].

[0023] [6] A metallic material selected by the method for selecting metallic materials described above [4].

[0024] [7] An automotive component that uses the metallic material described above [6].

[0025] Invention Effects

[0026] According to the present invention, a method for evaluating the delayed fracture characteristics of metallic materials is provided, which can accurately evaluate, for example, the delayed fracture characteristics of metallic materials used in atmospheric corrosion environments such as those used in automobile driving, caused by hydrogen penetrating into the interior of the metallic material due to atmospheric corrosion, which is dominated by chlorides.

[0027] Furthermore, the evaluation method for delayed fracture characteristics of metallic materials according to the present invention can obtain information needed to determine whether a metallic material will experience delayed fracture in a real-world application environment, such as design guidelines (strength, composition, etc.) for materials that experience delayed fracture in a real-world application environment. Attached Figure Description

[0028] Figure 1 This is a schematic diagram illustrating an example of the method for evaluating the delayed fracture characteristics of metallic materials according to the present invention.

[0029] Figure 2 This is an example of an image schematically showing the distribution of droplets on the evaluation surface of a metallic material.

[0030] Figure 3 This is a schematic diagram illustrating the case where a shielding component is disposed between the spray nozzle and the metal material in the evaluation method for delayed fracture characteristics of the metallic material of the present invention.

[0031] Figure 4 This diagram schematically illustrates how the sprayed liquid in the atmosphere re-adheres onto the evaluation surface when the distance between the shielding component and the evaluation surface of the metal material is changed.

[0032] Figure 5This figure illustrates one embodiment of the corrosion test cycle for evaluating the delayed fracture characteristics of metallic materials according to the present invention.

[0033] Figure 6 This figure illustrates another embodiment of the corrosion test cycle for evaluating the delayed fracture characteristics of metallic materials according to the present invention.

[0034] Figure 7 This is a schematic diagram of a test piece used to evaluate the delayed fracture characteristics in the embodiments. Detailed Implementation

[0035] First, the inventors' insights will be explained. Patent Document 1 describes a method for evaluating the delayed fracture characteristics of metallic materials used in atmospheric corrosion environments, caused by hydrogen penetrating into the interior of the metallic material along with atmospheric corrosion. Therefore, the inventors evaluated the delayed fracture characteristics of two high-strength steel plates (steel 1 and steel 2) of grade 1470 MPa under the following corrosion test cycles according to the method described in Patent Document 1, by changing the applied stress to be equivalent to YS (yield stress) and 0.9YS to 0.5YS. Here, the tensile strength (TS) of steel 1 is 1480 MPa and the yield point (YP) is 1190 MPa, and the TS of steel 2 is 1510 MPa and the YP is 1220 MPa.

[0036] Specifically, cold-rolled steel sheets with a thickness of 1.4 mm were cut into strips 35 mm wide and 100 mm long. To remove residual stress from the cutting process, the strips were ground until the width was reduced to 30 mm, and then strip-shaped test pieces were prepared. These strip-shaped test pieces were then ultrasonically cleaned in toluene for 5 minutes and bent 180° with a radius of curvature of 4 mmR. The shape of the test pieces was then fixed in this state using bolts and nuts. Furthermore, to vary the applied stress, test pieces were prepared with the inner spacing of the bent strip-shaped test pieces adjusted to a specified distance. The tests lasted for a maximum of 63 days, with daily observation of cracks to confirm the presence or absence of cracks. Additionally, the delayed fracture characteristics of the same test piece were evaluated in a real-world environment (Okinawa) (exposure test (1 year)). The results are shown in Table 1.

[0037] (Conditions for corrosion test cycles)

[0038] [The process of attaching chlorides to metallic materials]

[0039] Atmosphere

[0040] Chloride types: NaCl

[0041] • Adhesion amount: 1000~10000mg / m 2

[0042] • Adhesion method: Spraying

[0043] [A process that combines the drying and wetting processes into one cycle, and performs this cycle at least once.]

[0044] • Drying process conditions: temperature 30℃, humidity 30%RH, holding time 2 hours

[0045] • Transition time from drying to wetting process: 2 hours (excluding the holding time of the humidity holding process described below); humidity change rate: 30%RH / hour

[0046] • Conditions for the wetting process: Temperature 30℃, Humidity 90%RH, Holding time 2 hours

[0047] • Transition time from wetting to drying: 2 hours (excluding the holding time of the humidity holding process described below); humidity change rate: 30%RH / hour

[0048] • Humidity maintenance conditions: 55% RH, maintenance time 2 hours

[0049] • Cycle sequence: Drying process → Humidity maintenance process → Wetting process → Humidity maintenance process → Drying process

[0050] [Table 1]

[0051] Table 1 shows that, in the evaluation of delayed fracture characteristics in actual environments, steel 1 has a higher lower limit stress value for crack initiation compared to steel 2, indicating superior delayed fracture characteristics. Furthermore, when evaluating the delayed fracture characteristics of high-strength steel plates using the method described in Patent Document 1, under conditions of high chloride adhesion (chloride adhesion: 7000–10000 mg / m³),... 2 The results of the delayed fracture characteristics evaluation in actual environments differ from those in steel 2, showing either superior delayed fracture characteristics or identical delayed fracture characteristics between steel 1 and steel 2. This indicates significant fluctuations in the delayed fracture characteristics results. In other words, the method described in Patent Document 1 sometimes fails to accurately evaluate delayed fracture characteristics in actual environments. The inventors conducted a detailed investigation into this issue. The results revealed that the adhesion state of the chloride in the process of attaching chloride-based components to the metal material (the chloride attachment process) has a significant impact.

[0052] Specifically, the inventors have obtained the following insights: when attaching chloride-based components to metallic materials, there is a tendency for a more uniform distribution of chloride on the surface of the metallic material (evaluation surface) to result in smaller fluctuations in the evaluation results. Controlling not only the amount of chloride attached but also its distribution is important for conducting appropriate evaluations. In particular, the inventors have obtained the following insights: the distribution of salt water droplets attached to the surface of the metallic material at the beginning of the evaluation test significantly contributes to the uniformity of the entire evaluation test. By ensuring a uniform distribution of the initial (first) salt water droplets on the evaluation surface, fluctuations in the evaluation test results can be reduced.

[0053] Furthermore, the inventors believe that in order to improve the accuracy of the evaluation method for the delayed fracture characteristics of metallic materials, it is important to uniformly attach chlorides to the evaluation surface of the metallic material before corrosion. Therefore, it is important to control the distribution of chloride-containing aqueous solution droplets on the evaluation surface of the metallic material (droplet attachment distribution) during the chloride attachment process in the evaluation test, and various studies have been conducted, thus leading to the completion of this invention. This invention is based on the above insights.

[0054] In the evaluation method for delayed fracture characteristics of metallic materials of the present invention (hereinafter also referred to as the evaluation method of the present invention), a process comprising a chloride adhesion process (A) and a corrosion process (B) is performed at least once.

[0055] In the evaluation method of the present invention, it is preferable to apply stress to the metallic material. Methods for applying stress to the metallic material include processing methods (processing methods). Examples of such processing methods include bending, bulging, stretching, and torsion. Furthermore, methods such as using bolts to fix the material in a stressed shape, or utilizing residual stress after processing, can also be used. In the evaluation method of the present invention, the metallic material subjected to stress as described above can be subjected to at least one (or two) processes including a chloride adhesion process (A) and a corrosion process (B). Additionally, in the evaluation method of the present invention, after performing at least one process including a chloride adhesion process (A) and a corrosion process (B), the state of the metallic material can be confirmed, and the delayed fracture characteristics of the metallic material can be evaluated based on the confirmed state. This confirmation can be performed, for example, by visually observing the presence and extent of cracks in the metallic material.

[0056] Hereinafter, examples of embodiments of the evaluation method of the present invention will be described. However, the present invention is not limited to the following examples.

[0057] (Metallic materials)

[0058] First, the metallic material used in the evaluation method for the delayed fracture characteristics of the metallic material provided in this embodiment (hereinafter also referred to as the evaluation method of this embodiment) will be described. Examples of the metallic material include steel, but it is not limited to this; metallic materials such as Ti and Al can also be used. Furthermore, the metallic material may have a coating layer on its surface. Examples of coating layers include organic layers, inorganic layers, and mixtures of organic and inorganic materials. The coating layer may be a single layer or multiple layers. Examples of metallic materials with a coating layer on their surface include metallic materials where a chemical conversion treatment, such as zinc phosphate treatment, is applied to the surface of the metallic material to form a chemical conversion treatment layer, and then electrophoretic coating or the like is applied thereon to form a coating layer.

[0059] The form of the metallic material is not particularly limited; for example, it can be a sheet, bar, or tube. However, the evaluation method of this embodiment is applicable to the evaluation of thinner sheets or tubes, so sheets or tubes are preferred as the evaluation object.

[0060] Furthermore, in the evaluation method of this embodiment, stress is applied to the metallic material. The methods described above can be cited as examples of methods for applying stress to the metallic material.

[0061] In this embodiment, to evaluate the delayed fracture characteristics of a metallic material, a chloride deposition process (A) and an etching process (B) are performed on the metallic material under stress. Then, after each of the above processes is performed more than once, the delayed fracture characteristics are evaluated by checking whether there are cracks in the metallic material and their extent.

[0062] The following is a description of each process.

[0063] (Chloride Adhesion Process (A))

[0064] The chloride adhesion process (A) aims to achieve a chloride adhesion concentration of 1000–20000 mg / m³. 2 The process involves attaching droplets of an aqueous chloride-containing solution to the evaluation surface of a metal material. Furthermore, in the evaluation method of this embodiment, at least in the initial (first) chloride attachment step (A), the distribution of droplets of the aqueous chloride-containing solution on the evaluation surface of the metal material (droplet attachment distribution) is such that the average contact area of ​​the droplets on the evaluation surface of the metal material is 0.1 mm. 2 Above and below 3.0mm 2 The total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is between 40% and 80%, and the standard deviation of the contact area of ​​the droplets on the evaluation surface of the metal material is 3.0 mm. 2 the following.

[0065] Chloride adhesion amount: 1000~20000 mg / m³ 2 >

[0066] The amount of chloride adhering to the metal material (the amount of chloride solids excluding solvents such as water) is 1000–20000 mg / m³. 2 The above-mentioned adhesion amount corresponds to the assumed chloride adhesion amount under actual atmospheric corrosion conditions during vehicle operation. When the above-mentioned adhesion amount is less than 1000 mg / m³, 2 In such corrosive environments, corrosion is almost nonexistent, resulting in minimal hydrogen generation and penetration into the metallic material, thus reducing the likelihood of delayed fracture. On the other hand, the aforementioned adhesion amount exceeds 20000 mg / m². 2 At that time, the corrosion rate deviated significantly from that in a real environment, constituting an excessive durability test and thus failing to meet the intended purpose. Therefore, the aforementioned adhesion amount of 20000 mg / m² is appropriate. 2 The following is based on the perspective of simulating the corrosion morphology in the actual atmospheric corrosion environment of automobile driving and promoting corrosion. Therefore, the aforementioned adhesion amount is preferably greater than 5000 mg / m³. 2 Furthermore, based on the above viewpoint, the preferred adhesion amount is 12000 mg / m³. 2 the following.

[0067] It should be noted that the amount of chloride adhering can be calculated by multiplying the mass difference of the test subject (metal material) before and after the chloride-containing aqueous solution in the chloride adhering process (A) by the chloride concentration of the chloride-containing aqueous solution, and then dividing by the evaluation surface area of ​​the test subject. It should also be noted that when measuring the mass difference, if the chloride-containing aqueous solution adheres to areas outside the evaluation surface of the test subject, appropriate measures can be taken such as shielding the areas outside the evaluation surface or wiping away the chloride-containing aqueous solution adhering to those areas. Furthermore, when changing the amount of chloride adhering, the amount of chloride-containing aqueous solution applied to the metal material can be controlled, for example, by changing the chloride concentration of the chloride-containing aqueous solution or by changing the time the chloride-containing aqueous solution is applied (the process time of the chloride adhering process (A)).

[0068] In the chloride adhesion process (A), chloride is adhered to the metal material to obtain the desired amount of chloride. Preferably, the chloride contains one or more salts selected from sodium (NaCl), potassium (KCl), calcium (CaCl2), and magnesium (MgCl2) salts that are commonly found in the atmospheric environment where the metal material is used. It should be noted that in the chloride adhesion process (A), when adhering chloride to the metal material, a chloride-based component may also be adhered, containing both chloride and other components. Here, a chloride-based component refers to a component that, when converted to solid components, constitutes more than 50% by mass of the total components. Components other than chloride include, but are not limited to, sulfides and nitrate compounds. Considering the actual atmospheric corrosion environment, it is preferable to adhere a NaCl-based component (a component containing more than 50% by mass of NaCl) to the metal material.

[0069] Furthermore, when simulating the delayed fracture characteristics in areas where de-icing agents are frequently applied during winter, it is preferable that the chloride adhering to the metal material has a composition similar to that of the de-icing agents applied in that area. Examples of components with a composition similar to that of de-icing agents include: components mainly composed of CaCl2 (with CaCl2 accounting for more than 50% by mass of all components), components mainly composed of MgCl2 (with MgCl2 accounting for more than 50% by mass of all components), and components mainly composed of NaCl (with NaCl accounting for more than 50% by mass of all components).

[0070] Additionally, as chlorides that adhere to metallic materials, compositions containing two or more metal salts can also be used. Examples of compositions containing two or more metal salts include: SAE J2334 (0.5% by mass NaCl - 0.1% by mass CaCl2 - 0.075% by mass NaHCO3), artificial seawater (2.5% by mass NaCl - 0.5% by mass MgCl2 - 0.12% by mass CaCl2 - 0.07% by mass KCl, etc. (e.g., an aqueous solution of Aquamarine (a registered trademark) manufactured by Hachishu Pharmaceutical Co., Ltd.)).

[0071] There are no particular limitations on the method for attaching chlorides to metallic materials (chloride attachment method), as long as it is a method that can achieve the desired distribution of chloride-containing aqueous solution droplets on the evaluation surface of the metallic material. Examples of chloride-containing aqueous solutions include those containing chlorides as the main component (usually aqueous solutions such as salt water, hereinafter also referred to as salt water). The following explanation uses salt water as an example of a chloride-containing aqueous solution.

[0072] One method for chloride adhesion is spraying. Within spraying, methods using spray nozzles to adhere brine can be included. Types of spray nozzles include single-fluid spray nozzles (nozzles that atomize pressurized liquid for spraying) and two-fluid spray nozzles (nozzles that atomize liquid using high-speed fluids such as compressed air). Two-fluid spray nozzles can be further categorized into pressurized (liquid is pressurized and supplied to the nozzle) and suction (liquid is drawn up using compressed air for spraying). It is preferable to select a spray nozzle based on the viewpoint of uniform droplet adhesion distribution. Furthermore, since brine is used, the material of the spray nozzle is preferably a corrosion-resistant metal such as stainless steel.

[0073] The chloride concentration in the brine is not particularly limited. However, when using a spray nozzle to control the droplet distribution of the brine, if the brine with a chloride concentration of less than 2.0% by mass is used to adhere the brine to the metal material, the spraying time becomes longer in order to obtain a suitable amount of chloride adhesion. As a result, it is difficult to obtain the desired droplet distribution on the evaluation surface of the metal material. Therefore, the chloride concentration in the brine is preferably 2.0% by mass or more, more preferably 5.0% by mass or more. On the other hand, when using a brine with a chloride concentration exceeding 20% ​​by mass to adhere the brine to the metal material, chloride easily precipitates in the spray nozzle, causing nozzle clogging and making it difficult to spray brine droplets of a stable size. Therefore, it is difficult to obtain the desired droplet distribution on the evaluation surface of the metal material. As a result, the amount of chloride adhesion on the evaluation surface of the metal material varies depending on the location, with localized corrosion occurring in areas with high chloride adhesion and increased hydrogen intrusion. Therefore, the delayed fracture characteristics within the evaluation surface of the metal material change, and the evaluation accuracy of the delayed fracture characteristics decreases. This tendency becomes particularly significant when the amount of chloride adhesion is high. Therefore, the chloride concentration in the brine is preferably 20% by mass or less, and more preferably 15% by mass or less.

[0074] It should be noted that the chloride concentration in the brine should preferably be adjusted according to the target chloride deposition amount. A low-concentration brine is preferred when the chloride deposition amount is low, while a high-concentration brine is preferred when the chloride deposition amount is high. To reduce chloride deposition on the evaluation surface of the metal material using a high-concentration brine, the total brine spray volume must be reduced, which can easily lead to an excessively small average contact area of ​​the brine droplets adhering to the evaluation surface and an excessively large area ratio of the brine droplets relative to the total area of ​​the evaluation surface. Conversely, to increase chloride deposition on the evaluation surface of the metal material using a low-concentration brine, the total brine spray volume needs to be increased, which can easily lead to an excessively large average contact area of ​​the brine droplets adhering to the evaluation surface and an excessively large area ratio of the brine droplets relative to the evaluation surface area.

[0075] [Distribution of chloride-containing aqueous solution droplets adhering to the evaluation surface of the metal material in the initial chloride adsorption process (A)]

[0076] In the evaluation method of the present invention, it is necessary to control the distribution of brine droplets on the evaluation surface of the metal material in at least the initial (i.e., at least the first implementation) chloride adhesion step (A) within the range described below. It is considered that in the first chloride adhesion step, the areas on the evaluation surface of the metal material where brine exists primarily become the corrosion initiation points for that evaluation surface. Furthermore, in the second chloride adhesion step, brine spraying in a state where corrosion has occurred after the first chloride adhesion step and corrosion products have formed on the evaluation surface will cause wetting and spreading of the brine droplets on the evaluation surface of the metal material, even if the brine droplets are uniformly adhered to the evaluation surface of the metal material. Therefore, it is important to control the uniform distribution of brine droplets on the evaluation surface of the metal material in the first chloride adhesion step.

[0077] Figure 1 This is a schematic diagram illustrating an example of the evaluation method of this embodiment. For example... Figure 1 As shown, in the evaluation method of this embodiment, brine is sprayed from a spray nozzle, causing brine droplets to adhere to the evaluation surface of the metal material. At this time, in the initial chloride adhesion step (A), the distribution of brine droplets adhering to the evaluation surface of the metal material (droplet adhesion distribution) is controlled within a specified range.

[0078] Average contact area of ​​droplets on the evaluation surface of metallic materials: 0.1 mm 2 Above and below 3.0mm 2 >

[0079] In the evaluation method of this embodiment, in at least the first chloride adhesion step (A), the average contact area of ​​the droplets on the evaluation surface of the metal material (average contact area per droplet) is made 0.1 mm. 2 Above and below 3.0mm 2 The average contact area mentioned above is less than 0.1 mm. 2 At that time, due to the small size of the droplets, the target amount of chloride adhesion could not be achieved. Therefore, the average contact area was set to 0.1 mm. 2 The above. The preferred average contact area is 0.5 mm. 2 The above is more preferably set to 1.0mm. 2 That's all. On the other hand, the average contact area mentioned above is 3.0 mm. 2 At this point, the droplet adhesion distribution becomes uneven, and the fluctuations in the delayed fracture evaluation increase. Therefore, the average contact area is set to be less than 3.0 mm. 2The preferred average contact area is 2.8 mm. 2 Hereinafter, 2.5mm is preferred. 2 The following should be noted: The average contact area of ​​the droplets on the evaluation surface of the aforementioned metallic material can be determined by the measurement method described later.

[0080] <The area ratio of the total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metallic material: 40% or more and 80% or less>

[0081] In the evaluation method of this embodiment, in at least the first chloride adhesion step (A), the area ratio (total contact area ratio of droplets) of the total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is 40% or more and 80% or less. When the total contact area ratio of the droplets is less than 40%, the adhesion distribution of the droplets becomes uneven, and the fluctuation of the delayed fracture evaluation becomes larger. Therefore, the total contact area ratio of the droplets is set to 40% or more. The total contact area ratio of the droplets is preferably set to 50% or more, and more preferably 55% or more. On the other hand, when the total contact area ratio of the droplets is greater than 80%, adjacent droplets on the evaluation surface tend to combine with each other, and the average contact area of ​​the droplets (average contact area per droplet) tends to become coarser. Therefore, the total contact area ratio of the droplets is set to 80% or less. The total contact area ratio of the droplets is preferably set to 75% or less, and more preferably 70% or less. It should be noted that the total contact area ratio of the droplets can be measured by the measurement method described later.

[0082] Standard deviation of the contact area of ​​droplets on the evaluation surface of metallic materials: 3.0 mm 2 Following>

[0083] In the evaluation method of this embodiment, in at least the first chloride adhesion process (A), the standard deviation of the distribution of the contact area of ​​droplets on the evaluation surface of the metal material is 3.0 mm. 2 The following applies: The standard deviation of the contact area of ​​the droplets on the evaluation surface of the metallic material is greater than 3.0 mm. 2 At this point, the droplet adhesion distribution becomes uneven, and the fluctuations in the delayed fracture evaluation increase. Therefore, the standard deviation of the contact area of ​​the aforementioned droplets is set at 3.0 mm. 2 The standard deviation of the contact area of ​​the droplets is preferably set to 2.8 mm. 2 Hereinafter, 2.5mm is preferred. 2 The following should be noted: The standard deviation of the contact area of ​​the droplets described above can be determined by the measurement method described later.

[0084] Regarding the distribution of brine droplets adhering to the evaluation surface of the metal material (average contact area of ​​droplets, total contact area ratio of droplets, standard deviation of droplet contact area), the distribution of droplets on the entire evaluation surface of the metal material can be obtained and analyzed after the brine droplets are adhering to the evaluation surface of the metal material in the chloride adsorption process (A). The images can be acquired using a digital camera, microscope, optical microscope, etc. Alternatively, the images can be obtained from above the evaluation surface of the metal material (from...). Figure 1 The evaluation surface is obtained by photographing it (in the direction of the spray nozzle shown). The photographing of the evaluation surface can be performed inside the test chamber equipped with the spray nozzle, or after the metal material has been removed from the test chamber. Preferably, the latter method is used, where the metal material is removed from the test chamber equipped with the spray nozzle, and the evaluation surface of the metal material is photographed. Furthermore, the image is acquired immediately (within 30 seconds) after a droplet of salt water is applied to the evaluation surface of the metal material.

[0085] Figure 2 This is a diagram schematically showing the distribution of droplets on the evaluation surface of a metallic material obtained as described above. Figure 2 In the diagram, the area represented by circles represents the contact area of ​​the droplets. Based on this image, the average contact area of ​​the droplets (average contact area per droplet), the total contact area ratio of the droplets, and the standard deviation of the contact area of ​​the droplets are calculated through image analysis.

[0086] Here, the evaluation surface for metallic materials refers to the surface used to evaluate the delayed fracture characteristics of metallic materials. This evaluation surface can be appropriately determined based on the metallic material being evaluated. For example, if the metallic material is a sheet material, the surface of the sheet material opposite the spray nozzle can be used as the evaluation surface (see [reference]). Figure 1 Furthermore, when the metal material is subjected to stress, the surface of the stressed portion opposite the spray nozzle (equivalent to the plane view (top view) of the metal material when the direction in which the spray nozzle is located relative to the metal material is upward) can be used as the evaluation surface. More specifically, for example, as described later, when the metal material that has undergone bending is used as the evaluation object, the surface of the bent portion opposite the spray nozzle can be used as the evaluation surface (see...). Figure 7 ).

[0087] As a method for achieving the distribution of the aforementioned brine droplets, as described above, a method of using a spray nozzle to adhere the brine to the evaluation surface of a metallic material can be listed. As a spray nozzle, a two-fluid nozzle is preferred. Examples of two-fluid nozzles include KSMMS (product name) manufactured by Kyoritsu Alloy Manufacturing Co., Ltd., a two-fluid air atomizing nozzle (product name) manufactured by Spraying Systems Japan Co., Ltd., and a micro-mist generating nozzle (product name) manufactured by Ikenai Co., Ltd.

[0088] As an example of specific conditions when using a spray nozzle, the preferred distance is the distance from the tip of the spray nozzle to the evaluation surface of the metal material. Figure 1 The value of X in the figure is 10–30 cm. The preferred spray pressure from the spray nozzle is 0.05–0.7 MPa. The spray angle (…) Figure 1 The angle θ is preferably 30–120°. The spraying time of the brine is preferably less than 10 seconds. Furthermore, as mentioned above, the chloride concentration in the brine is preferably adjusted according to the target amount of chloride adhesion. It should be noted that, as... Figure 7 As shown, when a bent metal material is used as the evaluation object, the distance from the tip of the spray nozzle to the evaluation surface of the metal material is the shortest distance from the tip of the spray nozzle to the evaluation surface of the metal material.

[0089] As a method for distributing the aforementioned brine droplets, a particularly preferred method is to arrange a shielding member with an opening between a spray nozzle and a metal material, allowing droplets of the chloride-containing aqueous solution sprayed from the spray nozzle to pass through the opening of the shielding member and adhere to the evaluation surface of the metal material. Preferably, the opening of the shielding member has a shape and size that are substantially the same as the evaluation surface of the metal material. It should be noted that "substantially the same" means that when viewed from the spray side, the opening of the shielding member has the same outer peripheral shape and size as the evaluation surface, or the area of ​​the opening of the shielding member is within ±10% of the area of ​​the evaluation surface of the metal material. Furthermore, the shielding member preferably blocks everything except the evaluation surface of the metal material. That is, the shielding member is preferably such that when viewed from above, the evaluation surface of the metal material can be seen through the opening of the shielding member, while other parts are not visible (are blocked).

[0090] Figure 3 This is a schematic diagram illustrating the case where a shielding component is disposed between the spray nozzle and the metal material in the evaluation method of this embodiment. For example... Figure 3As shown, by configuring the aforementioned shielding component between the spray nozzle and the metal material, it is possible to prevent the spray liquid (atomized brine) that is sprayed from the spray nozzle but does not adhere to the evaluation surface of the metal material and floats in the atmosphere from adhering (re-adhering) to the evaluation surface of the metal material, which already has droplets attached after the brine spraying is completed. As a result, the desired droplet distribution on the evaluation surface of the metal plate can be achieved with high precision.

[0091] When using a shielding component, the distance X from the tip of the spray nozzle to the evaluation surface of the metal material is preferably 10 to 30 cm. Furthermore, it is preferable to keep the distance between the shielding component and the evaluation surface of the metal material (…). Figure 3 In this context, Y is set to be between 1 cm and 0.3 cm. When the distance Y is less than 1 cm, the spray liquid that did not adhere to the evaluation surface of the metal material but floated in the atmosphere remained near the evaluation surface of the metal material, thus reducing the re-adhesion suppression effect. Figure 4 (a)). On the other hand, when the distance Y is greater than 0.3X cm, the spray liquid passing through the opening of the shielding component disperses below the shielding component, and the re-adhesion suppression effect becomes smaller. Figure 4 (b) It should be noted that the distance Y mentioned above is the shortest distance from the shielding component to the evaluation surface of the metal material. It should also be noted that the material of the shielding component is not limited as long as it can prevent the sprayed liquid from passing through. Examples of materials include resin, ceramics, metal, and wood. The shielding component can be processed from these materials for use.

[0092] As described above, in the evaluation method of this embodiment, it is important to control the uniformity of the distribution of brine droplets on the evaluation surface of the metal material in the initial (first) chloride adhesion process (A). This control of droplet distribution on the evaluation surface is implemented at least in the initial chloride adhesion process (A). Furthermore, the average contact area of ​​the droplets, the total contact area ratio of the droplets, and the standard deviation of the droplet contact area can be measured at the end of the initial chloride adhesion process (A) (within 30 seconds after the brine spray ends). Alternatively, a test specimen different from the test specimen provided for testing can be used, with conditions pre-set to achieve the specified average contact area of ​​the droplets, the total contact area ratio of the droplets, and the standard deviation of the droplet contact area, and the evaluation test of the test specimen can be performed under the same conditions. It should be noted that in subsequent chloride adhesion processes (A), chloride adhesion can be performed under the same conditions as the initial chloride adhesion process (A), or, within the range where a specified amount of chloride adhesion can be obtained, under conditions different from the initial chloride adhesion process (A). Preferably, conditions are pre-set to achieve a specified average contact area of ​​droplets, total contact area ratio of droplets, and standard deviation of droplet contact area, and the initial chloride adhesion process (A) is performed under these conditions. Furthermore, if the chloride adhesion process (A) is performed more than twice, it is preferable to perform subsequent chloride adhesion processes (A) under these pre-set conditions.

[0093] The chloride adhesion process (A) is preferably carried out in an atmosphere with a relative humidity Ha1 of 30% or higher. When the relative humidity Ha1 in the chloride adhesion process (A) is less than 30%, especially when using a spray nozzle to spray droplets containing an aqueous solution of chloride, the droplets sprayed from the spray nozzle tend to dry before reaching the evaluation surface of the metal material. As a result, it sometimes becomes difficult to control the distribution of droplets to achieve the desired effect on the evaluation surface of the metal material. Furthermore, the chloride adhesion process (A) is preferably carried out in an atmosphere with a relative humidity of 80% or lower. When the relative humidity in the chloride adhesion process (A) is greater than 80%, the droplets adhering to the metal material tend to become coarse.

[0094] Furthermore, the chloride adsorption process (A) is preferably carried out in an atmosphere with a temperature Ta1 below 50°C. When the temperature Ta1 in the chloride adsorption process (A) exceeds 50°C, especially when using a spray nozzle to spray droplets containing an aqueous solution of chloride, the droplets sprayed from the spray nozzle tend to dry before reaching the evaluation surface of the metal material. As a result, it sometimes becomes difficult to control the distribution of droplets to achieve the desired effect on the evaluation surface of the metal material. On the other hand, there is no limitation on the lower limit of the temperature Ta1 as long as it is a temperature that can maintain the brine state. For example, the lower limit of the temperature Ta1 can be 20°C or 25°C.

[0095] The atmospheric corrosion environment is characterized by repeated cycles of wetting and drying states. Simulating these environmental changes is important for approximating the corrosion morphology in the actual environment of automobile driving. For example, in the case of steel materials, the corrosion products formed on steel materials will change depending on the wetting and drying states, and hydrogen will be generated during the change from a wetting state to a dry state or vice versa. Therefore, the conditions in the cycle of relative humidity change (corrosion process (B)) are also important in the evaluation of delayed fracture characteristics.

[0096] (Etching Process (B))

[0097] The etching process (B) is a process in which a cycle consisting of the following drying process (b1), the following wetting process (b2), the following transformation process (b3) and the following transformation process (b4) is performed as one cycle in an atmosphere with a temperature Tb1 below 60°C and within a certain range, and this cycle is performed at least once (once or twice).

[0098] <Temperature Tb1 of corrosion process (B): below 60℃ and within a certain range>

[0099] The corrosion process (B) is carried out in an atmosphere with a temperature Tb1 below 60°C and within a certain range. When the temperature Tb1 of the corrosion process (B) exceeds 60°C, not only will the evaluation be conducted in an environment that deviates from the actual corrosion environment of the metal material being used, but the corrosion mechanism may also change. Therefore, the temperature Tb1 of the corrosion process (B) is set to 60°C or below. Preferably, it is set to 50°C or below. On the other hand, there is no particular limitation on the lower limit of the temperature Tb1 of the corrosion process (B). When the temperature Tb1 of the corrosion process (B) is below 5°C, it is sometimes difficult to control the relative humidity in the corrosion test tank (constant temperature and humidity tank) used in the corrosion test. In addition, in order to significantly reduce the corrosion rate of the metal material, the evaluation time becomes longer. Therefore, the temperature Tb1 of the corrosion process (B) is preferably set to 5°C or above, and more preferably 10°C or above.

[0100] Furthermore, delayed fracture characteristics are strongly influenced by ambient (atmosphere) temperature. Therefore, in order to appropriately evaluate the delayed fracture characteristics of metallic materials considering the applicable location and operating environment of the metallic component, the temperature Tb1 of the aforementioned corrosion process (B) needs to be within a certain range. When the temperature Tb1 of the corrosion process (B) varies within ±5°C, the amount of hydrogen penetrating into the interior of the metallic material from the environment (hydrogen intrusion amount) can be evaluated with a variation of less than 30% relative to the hydrogen intrusion amount at the target ambient temperature, thus accurately evaluating the delayed fracture characteristics. When the temperature Tb1 of the corrosion process (B) varies within ±2°C, the variation of the hydrogen intrusion amount is within 15%. Therefore, the temperature Tb1 variation range of process (B) is preferably within ±5°C, more preferably within ±2°C.

[0101] [Drying process (b1)]

[0102] The drying process (b1) involves drying the metal material in an atmosphere with a relative humidity (Hb1) of 45% or less for 1.0 hour to 5.0 hours. The relative humidity (Hb1) of the drying process (b1) is set to 45% or less. This is to simulate a drying state that is one of the characteristics of an atmospheric corrosion environment. Furthermore, if the relative humidity (Hb1) of the drying process (b1) exceeds 45%, a longer holding time is required to fully dry the surface of the metal material, resulting in a longer evaluation time. The relative humidity (Hb1) of the drying process (b1) is preferably 40% or less. On the other hand, there is no particular limitation on the lower limit of the relative humidity (Hb1) of the drying process (b1). From the viewpoint of controlling relative humidity, the relative humidity (Hb1) of the drying process (b1) is preferably 20% or more. Additionally, if the components adhering to the surface of the metal material contain substances such as magnesium chloride or calcium chloride that exhibit deliquescence at lower relative humidity, it is preferable to set the relative humidity (Hb1) of the drying process (b1) even lower.

[0103] The drying process (b1) has a processing time (the time spent in an atmosphere with relative humidity Hb1) of 1.0 hour or more and 5.0 hours or less. When the drying process (b1) has a processing time of less than 1.0 hour, it is impossible to simulate an actual corrosive environment. On the other hand, when the drying process (b1) has a processing time of more than 5.0 hours, although it is possible to simulate an actual corrosive environment, the evaluation of delayed fracture characteristics is time-consuming.

[0104] [Wetting process (b2)]

[0105] The wetting process (b2) involves wetting a metallic material in an atmosphere with a relative humidity (Hb2) of 80% or higher for 1.0 hour to 5.0 hours. The relative humidity (Hb2) of the wetting process (b2) is set to 80% or higher. This is to simulate the wetting state, which is one of the characteristics of an atmospheric corrosion environment. When the relative humidity (Hb2) of the wetting process (b2) is less than 80%, the wetting effect is insufficient, and the actual corrosion environment cannot be simulated. Among chlorides, sodium chloride has the highest saturated critical vapor pressure, which is approximately 75-78% when converted to relative humidity. Therefore, for any chloride, as long as the relative humidity is set to 80% or higher, a water film will form on the surface of the metallic material due to the hygroscopic absorption of the chloride, maintaining a wetting state. Therefore, the relative humidity (Hb2) of the wetting process (b2) is set to 80% or higher. On the other hand, there is no particular upper limit to the relative humidity (Hb2) of the wetting process (b2), but it is preferable that the relative humidity (Hb2) of the wetting process (b2) is less than 98%. This is because when the relative humidity Hb2 reaches 98% or higher, the water film formed by condensation becomes too thick, making it easy to wash away attached chlorides. This phenomenon is particularly likely to occur when evaluating processed test subjects. Therefore, when evaluating processed test subjects, the relative humidity Hb2 of the wetting process (b2) is preferably set to less than 98%.

[0106] The processing time of the wetting process (b2) (the time spent in an atmosphere of Hb2 with a relative humidity of 80% or higher) is 1.0 hour or more and 5.0 hours or less. When the processing time of the wetting process (b2) is less than 1.0 hour, it is impossible to simulate the actual corrosive environment. On the other hand, when the processing time of the wetting process (b2) exceeds 5.0 hours, although it is possible to simulate the actual corrosive environment, the evaluation of delayed fracture characteristics is time-consuming.

[0107] [Transformation process (b3), Transformation process (b4)]

[0108] Transformation step (b3) is the process of changing the atmosphere from the aforementioned relative humidity Hb1 to the aforementioned relative humidity Hb2, and transformation step (b4) is the process of changing the atmosphere from the aforementioned relative humidity Hb2 to the aforementioned relative humidity Hb1. It is known that the amount of hydrogen penetrating into metallic materials, especially steel materials, increases when the relative humidity changes. That is, in transformation steps (b3) and (b4), a large amount of hydrogen penetrates into the interior of the steel material. The reason for this increase in hydrogen penetration into the metallic material when the relative humidity changes is not necessarily clear, but it can be considered as follows: In the case of transformation step (b3), which is the process of changing the atmosphere from the aforementioned relative humidity Hb1 to the aforementioned relative humidity Hb2, the chlorides present on the surface of the metallic material begin to absorb moisture due to deliquescence, and corrosion of the metallic material begins. It is known that the corrosion products present on the surface of the metallic material change at this time, and it is assumed that hydrogen is generated along with this change in corrosion products. Furthermore, in the transition process (b4), which involves changing the atmosphere from the aforementioned relative humidity Hb2 to the aforementioned relative humidity Hb1, the moisture becomes a concentrated solution containing chlorides and metal ions dissolved due to corrosion, and in the case of steel materials, it contains a large amount of iron ions, thus the pH of the solution is considered to decrease. That is, it is considered that the solution in the drying process contains a large amount of hydrogen ions, making it easier for hydrogen to penetrate into the metal material. Therefore, in the transition processes (b3) and (b4), the rate of change of relative humidity is kept to 30% / hour or less. When the rate of change of relative humidity in the transition processes (b3) and (b4) is 30% / hour or less, hydrogen generated during corrosion can fully penetrate into the metal material, making it possible to properly evaluate the delayed fracture characteristics. On the other hand, there is no particular lower limit for the rate of change of relative humidity, but if the transition processes (b3) and (b4) are too long, the evaluation of the delayed fracture characteristics will require a long time. Therefore, the rate of change of relative humidity is preferably 1.5% / hour or more, and more preferably 10% / hour or more.

[0109] The method for evaluating the delayed fracture characteristics of metallic materials according to the present invention aims to simulate the diurnal variation of relative humidity in a real environment. Therefore, when the processing time (time of one cycle) of the corrosion process (B) simulating diurnal relative humidity variations in a real environment exceeds 24 hours, it means that corrosion is slower than in a real environment, thus requiring a long evaluation time for the delayed fracture characteristics. That is, the processing time of the corrosion process (B) is preferably set to 24 hours or less. To facilitate evaluation, the processing time of the corrosion process (B) is more preferably set to 12 hours or less. On the other hand, shortening the processing time of the corrosion process (B) causes a sharp change in relative humidity, reducing the correlation with corrosion in a real environment, and sometimes resulting in inconsistencies with the delayed fracture characteristics results in a real environment. Therefore, the processing time of the corrosion process (B) is preferably set to 5 hours or more.

[0110] In the evaluation method of the present invention, the chloride adhesion process (A) and the corrosion process (B) are each performed at least once. The chloride adhesion process (A) can be configured in each cycle of the corrosion process (B) at a random number of times, or it can be configured in each cycle of the corrosion process (B) at a predetermined number of times. It should be noted that there is no particular upper limit to the number of times the process comprising the chloride adhesion process (A) and the corrosion process (B) is performed. For example, the process comprising the chloride adhesion process (A) and the corrosion process (B) can be repeatedly performed until cracks appear in the metal material. Alternatively, a test period of days can be predetermined, and the process can be performed a number of times corresponding to that test period. The number of times the process is performed can be appropriately set, for example, by simulating corrosion patterns in a real environment. As an example, the process can be set to 200 times or less, or it can be set to 100 times or less.

[0111] Next, the process that includes the chloride adhesion process (A) and the corrosion process (B) will be described. Figure 5 This is a diagram illustrating one embodiment of the corrosion test cycle of the evaluation method of the present invention. Figure 5 The corrosion test cycle shown illustrates an example of a corrosion test cycle in which the chloride adhesion process (A) and the corrosion process (B) are each performed once. In this example, the corrosion process (B) consists of a process that includes a drying process (b1), a conversion process (b3), a wetting process (b2), and a conversion process (b4) as one cycle.

[0112] The corrosion cycle following the chloride adhesion process (A) preferably begins with the drying process (b1). By drying the brine adhering to the chloride adhesion process (A) in the drying process (b1), the starting point of condensation is evenly dispersed when humidity rises, which can reduce fluctuations in the evaluation of delayed fracture characteristics. When the corrosion cycle begins with the conversion process (b3), wetting process (b2), or conversion process (b4), the starting point of condensation is easily unevenly dispersed due to reasons such as insufficient drying of the brine adhering to the chloride adhesion process (A) or the brine adhering to the chloride adhesion process becoming coarse due to moisture absorption in a high humidity environment. Therefore, it is preferable to avoid starting the corrosion cycle (B) from a process other than the drying process (b1).

[0113] In the case of a cycle of corrosion process (B) after chloride adhesion process (A) and chloride adhesion process (A) is performed again, it is preferable to add water washing process (C) before chloride adhesion process (A). Figure 6This diagram illustrates an example of a corrosion test cycle in which a corrosion process (B) is performed after a chloride deposition process (A), and a water washing process (C) is performed before the chloride deposition process (A) is repeated. When the chloride deposition process (A) is repeated without the water washing process (C), there is a tendency for a higher amount of chloride deposition and a greater amount of chloride accumulated on the surface of the metal material, sometimes making it impossible to maintain the same corrosion environment. Therefore, it is possible to evaluate delayed fracture characteristics under conditions different from the intended corrosion environment. Therefore, it is preferable to add a water washing process (C) before the chloride deposition process (A) is repeated. It should be noted that the water washing process (C) is a process of washing the evaluation surface of the metal material. The water washing method in the water washing process (C) is not particularly limited; for example, methods such as spraying water onto the evaluation surface of the metal material from a spray nozzle or immersing the metal material in water to wash the evaluation surface can be listed.

[0114] In the evaluation method of the present invention, after performing the above-mentioned chloride adhesion process (A) and corrosion process (B) more than once, the state of the metal material (whether there are cracks in the metal material and their degree, etc.) is confirmed, and the delayed fracture characteristics of the metal material are evaluated based on the confirmed state of the metal material.

[0115] Furthermore, the method for selecting metallic materials according to the present invention includes: an evaluation step of evaluating the delayed fracture characteristics of a metallic material using the aforementioned evaluation method for the delayed fracture characteristics of metallic materials; and a selection step of selecting a metallic material based on the evaluation results obtained in the aforementioned evaluation step. For metallic materials subjected to stress, by performing the aforementioned evaluation step, the relationship between the conditions of the corrosion test (temperature, relative humidity, amount of chloride adhesion, etc.) and the delayed fracture characteristics (the presence and extent of delayed fracture (test time for crack formation, etc.)) is obtained. Furthermore, the stress applied to the metallic material can be varied, and this relationship can be obtained under one or more of the aforementioned corrosion test conditions. Then, these relationships can be used to classify the metallic materials. Then, metallic materials suitable for shipment, etc., can be selected from the aforementioned classifications based on the usage environment of the metallic material and the stress applied to the component. It should be noted that the aforementioned selection step can also be performed based on whether the metallic material supplied to the aforementioned evaluation step meets a predetermined criterion. In this case, for example, in the aforementioned selection step, if the metallic material supplied to the aforementioned evaluation step meets the predetermined criterion, the metallic material can be selected. Examples of such criteria include, for instance, the presence or absence of crack formation, the number of days since crack formation, etc. The metal material selected by the method of selecting metal materials according to the present invention exhibits excellent adaptability to the operating environment and applied stress. Furthermore, automotive components using the aforementioned metal material exhibit excellent adaptability to the operating environment and applied stress.

[0116] The manufacturing method of the component of the present invention includes a step of processing a metal material selected by the above-described method to manufacture the component. The processing described above is not particularly limited, and various metal processing methods such as forming can be listed. As the above-described component, an automotive component is preferred.

[0117] Example

[0118] The present invention will be described below with reference to the embodiments shown. However, the present invention is not limited to the following embodiments.

[0119] (Metallic materials)

[0120] As metallic materials, cold-rolled steel sheets (steel A, steel B, and steel C) with different strengths as shown in Table 2 were prepared. The sheet thickness was 1.4 mm. Here, the delayed fracture characteristics of the above-mentioned cold-rolled steel sheets were evaluated in the inventive examples and comparative examples. The above-mentioned cold-rolled steel sheets were cut into widths of 35 mm and lengths of 100 mm. In order to remove the residual stress during shearing, they were ground until the width became 30 mm to make strip-shaped test pieces. The obtained strip-shaped test pieces were immersed in toluene for ultrasonic cleaning for 5 minutes, and then bent at 180° with a radius of curvature of 4 mmR. In this state, the shape of the test pieces was fixed by bolts and nuts to obtain... Figure 7 The test piece used to evaluate the delayed fracture characteristics is shown. As the test piece used to evaluate the delayed fracture characteristics (hereinafter referred to as "test piece" for ease of explanation), the strip test piece is bent at 180° with a radius of curvature of 4 mmR. By adjusting the inner spacing of the strip test piece after bending, the load stress is equivalent to 0.7 YS. Five such test pieces are made.

[0121] [Table 2]

[0122] (Corrosion test cycle)

[0123] For the above test pieces, a corrosion test cycle (corrosion test) consisting of the following chloride adhesion process (A) and corrosion process (B) was conducted. Details of the conditions for this corrosion test cycle are shown in Table 3. In the chloride adhesion process (A), a two-fluid spray method was used to spray an aqueous solution containing chlorides of the types shown in Table 3 and adjusted to the concentrations shown in Table 3. The distance between the spray nozzle and the evaluation surface of the test piece (…) Figure 3 X was set to 30 cm. The spray pressure of the spray nozzle was set to 0.2 MPa. The spray time of the brine was set to 5 seconds. Furthermore, a shielding component was placed between the spray nozzle and the test piece, and the distance between the shielding component and the evaluation surface of the metal material was set to... Figure 3The Y) in the diagram represents various positions from which the chloride-containing aqueous solution is sprayed. It should be noted that the shielding component has an opening with the same shape and size as the evaluation surface of the test piece, and can shield the test piece from the evaluation surface when viewed from above (at the spray nozzle position). It should also be noted that for No. 24 in Table 3, instead of a two-fluid spray, the chloride-containing aqueous solution is applied to the evaluation surface using a manually operated sprayer via atomization.

[0124] Regarding the amount of chloride adhering, the mass difference of the test piece before and after the brine spray is calculated, divided by the evaluation surface area of ​​the test piece, to calculate the amount of aqueous solution adhering. The amount of chloride adhering is then calculated from the chloride concentration of the aqueous solution. Regarding the droplet distribution on the evaluation surface, after the initial chloride adhering step (A) (within 30 seconds after the spraying of the chloride-containing aqueous solution), an image of the evaluation surface is acquired from above using a digital camera, and the distribution is determined through image analysis. It should be noted that subsequent chloride adhering steps (A) are performed under the same conditions as the initial chloride adhering step (A). The corrosion step (B) is performed sequentially as drying step (b1) → transformation step (b3) → wetting step (b2) → transformation step (b4), with each of these four steps considered as one cycle. It should be noted that in this embodiment, the temperature variation range of the corrosion step (B) is set to within ±5°C. In addition, in this embodiment, the following corrosion test cycle is used: a corrosion process (B) is performed after the chloride adhesion process (A), and a water washing process (C) is performed before the chloride adhesion process (A) is performed again. That is, in this embodiment, the delayed fracture characteristics are evaluated using the following corrosion test cycle.

[0125] Repeatedly perform the chloride deposition process (A) → corrosion process (B) → water washing process (C) cycle.

[0126] (Evaluation of delayed fracture characteristics)

[0127] The delayed fracture characteristic is evaluated by the number of days it takes for cracks to develop on the test piece. Specifically, during the corrosion test, the 180° bend of the test piece is visually observed once a day for the presence of cracks, and the number of days until cracks develop (crack development days) is recorded, with a maximum of 63 days. Here, crack development is defined as the occurrence of new cracks exceeding 1 mm relative to the surface condition of the machined area before the corrosion test. It should be noted that in the corrosion test used to evaluate this delayed fracture characteristic, for each embodiment (inventive example and comparative example), five samples are used, and the quality of the delayed fracture characteristic is determined by the number of test pieces that develop cracks by day 63 (crack development number).

[0128] The evaluation results of this delayed fracture characteristic are shown in Table 3. It should be noted that for steels A, B, and C, if the difference in the number of cracks is less than 1, the results are treated as the same.

[0129] The same test piece used in the corrosion test of this embodiment (test piece for delayed fracture evaluation) was provided for the exposure test conducted by the inventors in Okinawa Prefecture. The results showed that the delayed fracture characteristics of the cold-rolled steel sheets in question were (superior) steel A > steel B > steel C (inferior). That is, when evaluating the delayed fracture characteristics of steel A, steel B, and steel C under the same conditions, if the number of cracks generated is (few) steel A < steel B < steel C (many), then the evaluation method for delayed fracture characteristics is deemed appropriate.

[0130] As shown in Table 3, the evaluation method according to the present invention can accurately evaluate the delayed fracture characteristics caused by hydrogen penetrating into the interior of the metal material due to atmospheric corrosion, which is dominated by chlorides, for example, in the atmospheric corrosion environment of automobile driving, and can simulate the delayed fracture characteristics in the actual use environment.

[0131]

Claims

1. A method for evaluating the delayed fracture characteristics of metallic materials, wherein, Perform a process that involves at least one chloride deposition step (A) and an etching step (B). In the chloride adhesion process (A), the amount of chloride adhered is made to reach 1000-20000 mg / m³. 2 This method allows droplets of an aqueous solution containing chloride to adhere to the evaluation surface of the metallic material. In the corrosion process (B), in an atmosphere with a temperature Tb1 below 60°C and within a certain range, a cycle consisting of the following drying process (b1), wetting process (b2), transformation process (b3), and transformation process (b4) is considered as one cycle, and this cycle is performed at least once. Drying process (b1): A process of drying metal materials by maintaining them in an atmosphere with a relative humidity of less than 45% (Hb1) for more than 1.0 hour and less than 5.0 hours. Wetting process (b2): A process of wetting metal materials by maintaining an atmosphere with a relative humidity of 80% or higher (Hb2) for 1.0 hour to 5.0 hours. Transition process (b3): ​​A process of changing the atmosphere from relative humidity Hb1 to relative humidity Hb2 at a relative humidity change rate of less than 30% / hour. Transition process (b4): A process of changing the atmosphere from relative humidity Hb2 to relative humidity Hb1 at a relative humidity change rate of less than 30% / hour. At least in the initial chloride adhesion process (A), the distribution of droplets containing the chloride-containing aqueous solution on the evaluation surface of the metal material is such that the average contact area of ​​the droplets on the evaluation surface of the metal material is 0.1 mm. 2 Above and below 3.0mm 2 The total contact area of ​​the droplets relative to the area of ​​the evaluation surface of the metal material is 40% to 80% of the total contact area, and the standard deviation of the contact area of ​​the droplets on the evaluation surface of the metal material is 3.0 mm. 2 the following.

2. The method for evaluating the delayed fracture characteristics of metallic materials according to claim 1, wherein, In the chloride adhesion process (A), the aqueous solution containing chloride is sprayed using a spray nozzle. At this time, a shielding member with an opening is disposed between the metal material and the spray nozzle, so that droplets of the aqueous solution containing chloride sprayed from the spray nozzle pass through the opening of the shielding member and adhere to the evaluation surface of the metal material.

3. The method for evaluating the delayed fracture characteristics of metallic materials according to claim 1 or 2, wherein, The chloride adhesion process (A) is carried out in an atmosphere with a relative humidity of 30% or higher and a temperature of 50°C or lower.

4. A method for selecting a metallic material, comprising: The evaluation steps for evaluating the delayed fracture characteristics of metallic materials using the evaluation method for delayed fracture characteristics of metallic materials according to any one of claims 1 to 3; and The selection step for the metallic material is selected based on the evaluation results obtained in the evaluation steps.

5. A method for manufacturing a component, wherein, The component is manufactured by processing the metal material selected by the method for selecting metal materials as described in claim 4.

6. A metallic material selected by the method for selecting metallic materials according to claim 4.

7. An automotive component that uses the metallic material of claim 6.

Citation Information

Patent Citations

  • Method for evaluating delayed fracture property of metal material and metal material

    JP2016180658A